Pengaruh Absensi Elektronik (Face Recognition) dan Pengawasan terhadap Disiplin Kerja Pegawai di Balai Besar Pengembangan Pasar Kerja dan Perluasan Kesempatan Kerja Lembang - Annisa Nurmayanti; Rusman Frendika; Allya Roosallyn Assyofa (UNISBA Press, 2022)
Abstract. This study aims to determine 1) Electronic Attendance (face recognition) at the Center for the Development of the Job Market and Expansion of Employment Opportunities in Lembang. 2) Supervision at the Center for Labor Market Development and Expansion of Employment Opportunities in Lembang. 3) Work Discipline at the Center for Labor Market Development and Expansion of Employment Opportunities in Lembang. 4) Electronic Attendance (face recognition) for Work Discipline at the Center for Labor Market Development and Expansion of Lembang Job Opportunities. 5) Supervision of Work Discipline at the Center for Labor Market Development and Expansion of Lembang Job Opportunities. 6) Electronic Attendance (face recognition) and Supervision of Work Discipline at the Center for Labor Market Development and Expansion of Lembang Job Opportunities. Using descriptive analysis, the type of causal associative research and using a quantitative approach. Data collection techniques using questionnaires,observation, and documentation. The population in this study were the employees of the Center for the Development of the Labor Market and the Expansion of Employment Opportunities in Lembang, amounting to 98 people using simple random sampling technique in order to obtain a total sample of 77 respondents. The results showed that there was a positive and significant effect of electronic attendance (face recognition) and supervision on employee work discipline at the Center for Labor Market Development and Expansion of Employment Opportunities in Lembang. Abstrak. Penelitian ini bertujuan untuk mengetahui 1) Absensi Elektronik (face recognition) di Balai Besar Pengembangan Pasar kerja dan Perluasan Kesempatan Kerja Lembang. 2) Pengawasan di Balai Besar Pengembangan Pasar kerja dan Perluasan Kesempatan Kerja Lembang. 3) Disiplin Kerja di Balai Besar Pengembangan Pasar kerja dan Perluasan Kesempatan Kerja Lembang. 4) Absensi Elektronik (face recognition) terhadap Disiplin Kerja di Balai Besar Pengembangan Pasar kerja dan Perluasan Kesempatan Kerja Lembang. 5) Pengawasan terhadap Disiplin Kerja di Balai Besar Pengembangan Pasar kerja dan Perluasan Kesempatan Kerja Lembang. 6) Absensi Elektronik (face recognition) dan Pengawasan terhadap Disiplin Kerja di Balai Besar Pengembangan Pasar kerja dan Perluasan Kesempatan Kerja Lembang. Menggunakan analisis deskriptif, jenis penelitian asositif kausal dan menggunakan pendekatan kuantitatif. Teknik pengumpulan data menggunakan kuesioner, observasi, dan dokumentasi. Populasi pada penelitian ini yaitu pegawai Balai Besar Pengembangan Pasar Kerja dan Perluasan Kesempatan Kerja Lembang yang berjumlah 98 orang dengan menggunakan teknik sampling simple rando sampling sehingga diperoleh jumlah sampel sebanyak 77 responden. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan absensi elektronik (face recognition) dan pengawasan terhadap disiplin kerja pegawai di Balai Besar Pengembangan Pasar Kerja dan Perluasan Kesempatan Kerja Lembang.